Genetic control of systemic Leishmania major infections: dissociation of intrahepatic amastigote replication from control by the Lsh gene. - Mock, B A (1985)
Systemic disease induced by Leishmania major was estimated by microscopic examination of liver impression smears and determination of numbers of intrahepatic amastigotes in intravenously or subcutaneously infected inbred, hybrid, and congenic mice. The distribution of susceptible phenotypes among these mice, particularly the susceptibility of a strain congenic for Lshr, strongly suggested that Lsh, a gene which controls intrahepatic replication of Leishmania donovani, does not influence systemic disease by L. major.